Análisis de la incidencia del clima laboral en el rendimiento del talento humano de Emelnorte S.A – Agencia Otavalo - Bedón Bedón, Silvia Cristina (2020)
The aim of this project is to analyze the impact of the labor environment on the performance of the human staff of EMELNORTE - Otavalo Agency, considering that the labor environment promotes a good homogeneous coexistence in companies, and it is considered a central axis of organizations to reach quality levels according to competitiveness. The objectives that this study pretends to achieve are: to determine the factors that influence the working environment of company mentioned before, in order to assess them, establish the levels of performance that the human staff of the company has, to relate them to the work environment and analyze the correlation between the working environment and the performance of the human staff of EMELNORTE. The methods used are: qualitative and quantitative type, the correlational descriptive method and the non parametric inferential statistical design chi square. For the collection of information, interview and survey techniques were applied to the employees if the institution. From the results of the factors that influence the working environment of it. It is determined that the staff were agreed with these factors in the institution. The results of the performance achieved from the performance evaluation of the year 2018 concludes on the following rating scales: 4 workers corresponding to 13% have an excellent rating scale, 24 workers that means 74% have a very good rating, 4 workers that is 13% achieved a satisfactory qualification, the results of chi-square determine that it is accepted that the working environment if it affects the performance of the human staff of EMELNORTE SA – Otavalo Agency.